Remote Monitoring Real Time Air pollution - IoT (Cloud Based) - Karabatak, Murat; Mustafa, Twana; Hamaali, Chawan (Institute of Electrical and Electronics Engineers Inc., 2020)
Air pollution, contamination, and Leakage of Liquefied Petroleum Gas (LPG) produce perilous and dangerous effects on human starts and other living. Subsequently, the author built up a framework to monitor by cloud and associated with it, the LPG gas leakage, and send an alarm to clients of it. Temperature and Moistness sensor and MQ-6 gas sensors are utilized for detecting the degree of gas concentration awareness of a closed volume and to monitor the outcomes of ecological changes an IoT platform has been presented. This paper describes the structure of a usable model dependent on the Internet of Things (IoT) ideas for continuous monitoring of different environmental conditions utilizing certain normally accessible and lower-priced sensors and associated with the cloud. The things utilized in this paper were (HDT11, MQ6, ESP8266, ATMega328p, Internet, and RemoteXY cloud server). The different ecological conditions, for example, temperature, dampness, and Liquefied Petroleum Gas (LPG) are ceaselessly monitored for air pollution, prepared, and controlled by using an ATmega328p microcontroller with the assistance of a few sensors. Strong control alongside cloud-based manual control has been applied to a control system utilizing the RemoteXY cloud server. Caught data are communicated through the internet with an ESP8266 Wi-Fi module. The anticipated framework conveys sensor data to an API referred to as RemoteXY over an HTTP protocol. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: air pollution; Cloud; DHT11; ESP8266; Healthcare monitoring; Internet of Things-IoT; LPG; MQ-6; RemoteXY; sensor; Temperature & Humidity; wireless sensor networks